Ocular biometry in children and adolescent from age 4 to 17 years with intraocular lens power calculation in Sulaymaniyah city - Naz Othman Rashid; Bakhtiar Qadir HamaSalh; Diare Tahir Ali Mirza (Advanced Medical Journal)
Background and objectives: Ocular biometry is an essential method to measures the anatomical dimensions of the eye in adult and children. The objective is to detect the ocular biometric changes and intraocular lens power calculation in children and teenagers (4 to 17) years.